The Relationship of Physical Activity and Hypertension in the Elderly at the Limboto Health Center, Gorontalo Regency - Johan Arya Harun; Nasrun Pakaya; Nirwanto K. Rahim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Hypertension is one of the non-communicable diseases that is a global health problem because it can cause serious complications such as heart disease, stroke, and kidney failure. One of the factors that affect the increase in blood pressure is physical activity. Lack of physical activity can increase the risk of hypertension to a higher degree, especially in the elderly group. This study aims to determine the relationship between physical activity and the degree of hypertension in the elderly in the working area of the Limboto Health Center, Gorontalo Regency. The type of research used is quantitative with a correlational analytical design through a cross sectional approach. The study population was all Prolanis hypertension patients in the working area of the Limboto Health Center, with a sample of 75 respondents selected using the purposive sampling technique. The research instruments were in the form of physical activity questionnaires and blood pressure observation sheets. Data analysis was carried out using the Chi-Square test. The results showed that most of the respondents had poor physical activity as many as 44 respondents (58.7%) and the majority were in the category of degree 2 hypertension as many as 36 respondents (48.0%). The results of the statistical test showed a p-value of < 0.05, which means that there is a significant relationship between physical activity and the degree of hypertension. It was concluded that physical activity is related to the degree of hypertension in the elderly. People with hypertension are advised to increase physical activity regularly to help control blood pressure and prevent further complications.